Skin, hair, and nails [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 11 minute video shows the steps needed to examine the skin, hair, and nails, including the proper use of equipment. With the patient seated, it demonstrates how to inspect and palpate the skin, hair, and nails. The video shows expected findings and alerts the viewer to selected variations in pediatric and geriatric patients as well as differences between light-skinned and dark-skinned patients. In addition, it emphasizes teaching the patient to perform skin self-examination."--Publisher's website